Dan Bersama Rohmu: (Suatu Eksegese dan Katekese Liturgi) - Embu, Alfons No (Sekolah Tinggi Katolik Santo Yakobus Merauke, 2013)
TPE has been renewed and changed. One of the reason is the change of the instruction of liturgy text translation from its original Latin Misal text. Comme Le Prevoit (1969) favored sense translation. And Liturgiam Authenticam (2001) instead changed for literal translation. For the example that will be explained in this writing is the changed of Greeting translation, notably the people’s answer. The former translation is “Dan sertamu juga”, based on Insctruction Comme le Prevoit. The new translation is “Dan bersama rohmu”, based on the principal instruction of Liturgiam Authenticam. We need to explain the reason of the renewal translation, the biblical context and the interpretation of the text.